Measuring synaptic loss in early AD stages: Trajectories of SNAP25 and SYT1 using serial CSF sampling. (31st December 2021) - Duits, Flora H.; Brinkmalm, Ann; Scheltens, Philip; Blennow, Kaj; Zetterberg, Henrik; van der Flier, Wiesje M.; Teunissen, Charlotte E.
Abstract: Background: It is increasingly recognized that synaptic dysfunction plays an important role in Alzheimer pathology, already in an early phase. In this study we investigated the presynaptic biomarkers SNAP25 and SYT1 in early stages of AD. Using serial CSF samples in a cohort of memory clinic patients with detailed clinical follow‐up, we studied prognostic value, the association with cognitive decline and longitudinal trajectories of these biomarkers. Method: We included 150 subjects with subjective cognitive decline (SCD; 62±7 years), mild cognitive impairment (MCI; 66±8 years) and AD dementia (64±7 years) from the Amsterdam dementia cohort, based on availability of CSF at two time points (median[IQR] 2.1[1.4‐2.7] years) and clinical follow‐up of at least one year. CSF SNAP25 and SYT1 were analyzed using immunoprecipitation mass spectrometry. To assess differences in SNAP25 and SYT1 levels between diagnostic groups at baseline, change in biomarker levels over time and association with cognitive decline we used linear mixed models. We used Cox regression models to assess predictive value of baseline biomarker level for disease progression. Analyses were adjusted for age and gender, Cox models also for ATN biomarker status. Result: Table 1 shows the results of the linear mixed models. Baseline levels of SNAP25 were higher in AD dementia compared to SCD and MCI, SYT1 levels were similar between groups. Over time SNAP25 increased in SCD subjects (B[SE] 0.24[0.10], p<0.05), SYT1 decreased in AD dementia patients (B[SE] ‐2.6[0.8], p<0.01). In SCD and MCI subjects higher SNAP25 was associated with faster decline in MMSE over time (st.B[SE] ‐0.24[0.12], p<0.01 for SCD; ‐0.39[0.16], p<0.05 for MCI). For SYT1 there was an effect only for SCD subjects (st.B[SE] ‐0.18[0.07], p<0.01). Baseline SNAP25 was a significant predictor for conversion to MCI or AD in non‐demented subjects (HR[95%CI] 4.4 [2.1‐9.1]), even after addition of ATN status (HR[95%CI] 2.8 [1.1‐7.3]; table 2, figure 1). Conclusion: SNAP25 levels increased over time in SCD subjects, and both SNAP25 and SYT1 were associated with cognitive decline in early stages of AD. High levels of SNAP25 predicted conversion to AD dementia. Hence, they may have potential to be used for disease monitoring or as amyloid‐independent outcome measure in clinical trials.